Identifying an Organizational Culture Model/Framework for an Effective Approach to Quality Management: a Comprehensive Literature Review - Gibson Manalu (Jurnal Multidisiplin Madani, 2022)
Quality management (QM) is not a new concept, nor is it a collection of processes or practices. Nonetheless, with rapid global changes across industries and markets, effective QM practices are more important than ever. Implementing QM practices in any company or company cannot happen separately from the organizational culture of the company or company. The competitive values framework (CVF), the Denison model, the organizational culture inventory (OCI), and the organizational culture profile are the most popular models and frameworks for addressing organizational culture (OCP). Many researchers find it difficult to decide which model/framework to apply when studying organizational culture. This paper provides a comprehensive literature review on each of these models/frameworks based on Boolean search results. This allows research to compare and contrast each, resulting in a set of recommendations and future directions for researchers in this field